Partisipasi Politik Generasi Muda pada Pemilihan Umum Tahun 2024 - Khakim, Muhammad Salisul (Indonesian Journal Publisher, 2023)
This study aims to explain the political participation of the younger generation in preparing for the general election in 2024. This political participation is influenced by several factors, ranging from modernization, social class, intellectuals, elite conflict, to political decisions. Factors in political participation determine the quality of the political elite who will lead the country in the future. This study uses a qualitative and quantitative approach, with data collection through literature studies and through questionnaires that affect the influence of political participation for the younger generation on elections. This study shows that the role of the younger generation has a fairly high political participation role, namely as the main effort to change the role of the country for the better. However, what needs to be prepared at this time is not only to carry out socialization and political education on the use of voting rights in the general election in 2024, but what is more important is an understanding of the orientation and projections of political parties and political figures who will fill the constellation of a better state in the future.